Maroboduus Romanorum una hostis et amicus = Marbod - once an enemy and once a friend of Romanis - Olędzki, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Of all Suebian rulers known to us, the figure of Marbod has been best described by historiography and it is to him that the greatest number of works have been devoted. Marbod stayed in Rome in his youth and it was there that he won friendship, favours and protection from Augustus himself. About the year 8 B .C. Romans helped him to gain power and rule over Marcomanii and Quadi. It was probably at that time that he performed the role of the client ruler in the face of the Empire. However, he began to rule independently soon after that.
Keywords: Marbod (władca plemienia Markomanów; 30 p.n.e. - 37 n.e.); Markomanowie - 1 w. p.n.e.-1 w.; Kwadowie (Swebowie; germański lud zamieszkający w starożytności dorzecze rzek Nidda, Fulda i Lahn); Rzym; Regnum Marobodui; Marcomanni; Quadi; Rome; regnum Marobodui